TRAINING FUTURE PRIMARY SCHOOL TEACHERS TO DEVELOP STUDENTS' NATIONAL IDENTITY IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESSES (Comparative Professional Pedagogy, 2025)
The article is devoted to the theoretical substantiation and systematic analysis of the content of professional training of future primary school teachers in the context of developing the national identity of students with regard to European values. The focus of the study is on updating educational and professional programs in accordance with the requirements of the State Standard of Primary Education, the New Ukrainian School Concept, modern socio-cultural challenges and the cultural policy of the European Union. The author emphasizes the role of the primary school teacher as a key subject in the formation of students’ worldview orientations, capable of combining patriotism education with openness to democratic and humanistic European values.The relevance of integrating the content of European programs, practices and values into teacher education is substantiated. The main directions of the EU cultural policy in Ukraine (preservation of cultural heritage, inclusiveness, gender equality, intercultural communication, development of the cultural ecosystem) are identified and their educational potential in the context of teacher training is analyzed. The structure of the professional competencies of a teacher in accordance with the new Professional Standard “Teacher of a General Secondary Education Institution” (2024) is outlined, focusing on 12 competencies that are directly related to the development of national identity. The detailed characteristics of each of them are provided, taking into account the following components: abilities, knowledge, skills, communication, responsibility and autonomy.The article considers the possibilities of updating the content of disciplines of educational and professional programs, taking into account an interdisciplinary approach, combining patriotic and intercultural content, and introducing inclusive and digital technologies. Examples of thematic blocks for such disciplines as Pedagogy, Theory and Methods of Education, Fundamentals of Inclusive Education, and Methods of Teaching Educational Fields are presented.
Keywords: national identity; European values; primary education; teacher education; primary school teacher; primary school students; professional training; educational competencies; EU cultural policy; New Ukrainian School